Development of a JARE deep ice core drill system - Tanaka, Yoichi; Takahashi, Akiyoshi; Fujii, Yoshiyuki; Narita, Hideki; Shinbori, Kunio; Azuma, Nobuhiko; Watanabe, Okitsugu (1994)
P(論文) The final design of an electro-mechanical drill is very simple both in shape and in mechanism. It is a straight tube consisting of an antitorque section, motor and computer section, chip chamber and core barrel. Three cutters (rake angle : 30 to 40 degrees, pitch : 5 to 7mm) are attached to cut an ice core 94mm in diameter and bore hole 135mm in diameter. The maximum core length is 2.1m long. Chips are transported between the core barrel and the outer tube by spiral rim attached to the core barrel. No motor for sucking chips up to the chip chamber is installed. The chips are separated from liquid by the filter at top of the chip chamber, and are compacted to the density of 500kg/m^3. In the pressure tight electronics section, a computer, DC brushless motor (270V, 600W, 12000rpm) and reduction gear (1/170) are installed. The antitorque section has three leaf springs. A steel cable 7.7mm in diameter has been chosen. The actual drilling operation is easy, for in response to the cutter load, a switching signal (go or stop) can be sent from the relay computer to the winch controller. What an operator has to do is, before drilling, to set the winch speed at the proper value and set the threshold value of the cutter load, and, while drilling, check the motor current if it increases rapidly. departmental bulletin paper